Clinical effectiveness of nutrof total supplement for Dry age-related macular Degeneration - E. N. Eskina; A. V. Belogurova; M. A. Stepanova (Российский офтальмологический журнал)
The paper’s purpose is to assess visual functions in patients with dry age-related macular degeneration (AMD) who receive antioxidant Nutrof Total supplement. Three groups of patients over 50 were examined. The main group, AMD+, consisted of patients with dry AMD who took 1 capsule of the supplement once a day for 3 months. Control group 1, AMD-, was composed of patients with dry AMD who took no supplement at all and control group 2, Normal, was composed of healthy subjects who took 1 capsule once a day for 3 months. All subjects were subjected to a regular ophthalmologic examination supplemented by evaluation of photostress test recovery time, and measurement of the optical density of macular pigment (MPOD) and achromatic spatial contrast sensitivity (CS): all tests were taken prior to the study and repeated 1 and 3 months after the study’s start. Vision quality was assessed by a VFQ-25, 2000 version questionnaire. Groups AMD+ and Normal revealed a statistically significant improvement in uncorrected distance and near visual acuity and best-corrected distance visual acuity, MPOD increase, improved recovery of visual acuity after a photostress test, and improvement in achromatic CS in all spatial frequency ranges. AMD- patients revealed no positive effects of visual functions. The results of the study thus confirm the efficiency and usefulness of continuous Nutrof Total supplement administration for 3 months by dry AMD patients and all patients over 50 // Russian Ophthalmological Journal, 2016; 2: 90-5. doi: 10.21516/2072-0076-2016-9-2-90-95 .